Developing the Numerical Simulation of Multicomponent Alloy Solidification - V. P. Ginkin; S. M. Ganina; A. V. Kartavykh (Advanced Aspects of Engineering Research Vol. 16, 2021)
Multicomponent melt solidification has been studied using a non-equilibrium model, in which a Stefan problem with two boundaries is solved numerically, the boundaries being between the solid phase and the two-phase transition zone and between the two-phase transition zone and the liquid phase. A porous medium with variable porosity is used to depict the two-phase zone. By analogy with Darcy’s law, consideration is given to the additional force resisting melt flow due to porosity. The experiment on Sn-20 wt. % Pb binary alloy solidification by the process of downward-directed crystallization along the gravity vector was computer simulated. Shown in the paper are the results of a quasi two-dimensional benchmark experiment on horizontal (i.e., at the right angle to the gravity vector) directional solidification of a binary Sn-3 wt.%Pb alloy. The calculations were carried out using two crystallisation models: equilibrium and non-equilibrium crystallisation.The non-equilibrium model is shown to provide a more accurate representation of the thermal field evolution and solute distribution induced by natural convection.